Synthesis and Characterization of Silver Nanoparticles from the Leaf Stalk Extract of Moringa oleifera - R, Irwan; Teheni, Muhammad Tasjiddin; Syafriah, Waode (Indonesian Journal of Chemical Research, 2023)
The exploitation of plant extract as a reducing agent for synthetic silver nanoparticles has become the main focus of researchers. This study aimed to synthesize silver nanoparticles (AgNPs) from Moringa oleifera leaf stalk extract via bio-reduction. The AgNPs were characterized through ultraviolet-visible absorption spectroscopy (UV-Vis), Fourier transforms infrared spectroscopy (FTIR), and X-ray diffraction (XRD). The research results indicated that an increase in the initial AgNO3 concentration and incubation time had affected the absorption pattern of the surface plasmon resonance (SPR) trend of AgNPs. The results of the functional group analysis revealed the formation of the ketone group (1741 cm-1), which was derived from hydroxyl groups (3415 cm-1). The crystal structure of AgNPs was characterized using XRD. The estimation of the crystal measurement based on the Debye-Scherer equation was 15.59 nm, which was estimated as having a cube crystal form.